2014
DOI: 10.1590/2176-9451.19.1.055-059.oar
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental anomalies of number in different subphenotypes of isolated cleft palate

Abstract: ObjectiveThis study aimed at carrying out a radiographic analysis on the prevalence of dental anomalies of number (agenesis and supernumerary teeth) in permanent dentition, in different subphenotypes of isolated cleft palate pre-adolescent patients. MethodsPanoramic radiographs of 300 patients aged between 9 and 12 years, with cleft palate and enrolled in a single treatment center, were retrospectively analyzed. The sample was divided into two groups according to the extension/severity of the cleft palate: com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 10 publications
1
14
0
2
Order By: Relevance
“…There is still controversy regarding prevalence by gender. [5] It is also found differences in the prevalence of affected teeth, but there is agreement that the most affected tooth is the third molar. [8] The restorative treatment of patients with dental agenesis in most cases is multidisciplinary, as the spaces should be distributed in the best way so that they can have a better ratio of size and tooth width.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is still controversy regarding prevalence by gender. [5] It is also found differences in the prevalence of affected teeth, but there is agreement that the most affected tooth is the third molar. [8] The restorative treatment of patients with dental agenesis in most cases is multidisciplinary, as the spaces should be distributed in the best way so that they can have a better ratio of size and tooth width.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, spaces are kept for later work on the esthetic restoration. [5] Treatment in most cases is multidisciplinary, involving specialties such as orthodontics, dentistry, implant or prosthetic rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Diversos estudios señalan que las anomalías dentales son más frecuentes en pacientes con fisura labiopalatina que en la población en general 14,[16][17][18] . Pueden ser alteraciones de número, forma, tamaño, tiempo de formación, calcificación y erupción que podrían afectar tanto la dentición temporal como la permanente.…”
unclassified
“…It could be that the discrepancy between the parent and child is due to lack of communication, or extenuating familial circumstances. Silva et al (2014) found that better family relationships showed closer agreement between the parent and child, while a greater care-giving burden or heightened stress within the family, led to a greater disagreement within the dyad. Another reason for the discrepancy could be the parents' inability to recognize slow, incremental progress that the child has made, rather continuing to label the child has having significant challenges in his or her life that may have resolved.…”
Section: Dyad Outliersmentioning
confidence: 93%
“…Another area worthy of investigation is the role of parental mental health in communicating a child's quality-of-life. Silva et al (2014) examined quality of life and psychological problems as it related to children with asthma. It was observed that better family relationships showed closer agreement between the parent and child, while a greater care-giving burden (e.g: more severe illness) lead to a greater disagreement within the dyad.…”
Section: Further Researchmentioning
confidence: 99%